ANALISIS PENGARUH MODAL KERJA DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PERUSAHAAN CONSUMER GOODS PADA SAAT PANDEMI COVID-19 - Stenly Jacobus Ferdinandus; Wellem Kaihatu (Pusat Riset dan Inovasi Nasional, 2021)
The COVID-19 pandemic that has occurred in Indonesia since the beginning of 2020 has become a serious problem for the Indonesian economy, including the consumer goods industry listed on the Indonesia Stock Exchange. Thus, the objectives of this study were (1) to determine the effect of using working capital on the profitability of companies in the consumer goods industry sector during the COVID-19 pandemic. (2) to determine the effect of accounts receivable turnover on the profitability of companies in the consumer goods industry sector during the COVID-19 pandemic. This study was a descriptive research by testing the hypothesis through a quantitative approach. The technique used to determine the number of samples was purposive sampling. Based on such technique, a sample of 9 consumer goods companies listed on the Indonesia Stock Exchange was obtained. This research employed primary data and secondary data. The analytical method used was regression on panel data analysis.Verificatively, the results of this study show that: (1) Working capital turnover has a positive and significant impact on the profitability of consumer goods companies listed on the Indonesia Stock Exchange during the COVID-19 pandemic. (2) Accounts Receivable Turnover has an insignificant positive effect on the profitability of consumer goods companies listed on the Indonesia Stock Exchange during the COVID-19 pandemic.